2018
DOI: 10.1038/s41598-018-21876-y
|View full text |Cite
|
Sign up to set email alerts
|

Foxm1 controls a pro-stemness microRNA network in neural stem cells

Abstract: Cerebellar neural stem cells (NSCs) require Hedgehog-Gli (Hh-Gli) signalling for their maintenance and Nanog expression for their self-renewal. To identify novel molecular features of this regulatory pathway, we used next-generation sequencing technology to profile mRNA and microRNA expression in cerebellar NSCs, before and after induced differentiation (Diff-NSCs). Genes with higher transcript levels in NSCs (vs. Diff-NSCs) included Foxm1, which proved to be directly regulated by Gli and Nanog. Foxm1 in turn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Many studies have revealed that FOXM1, a carcinogenic transcriptional factor, has a critical function in the pathogenesis of various cancers, including liver cancer [43,44]. However, the FOXM1-related upstream regulatory events in LCSCs are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that FOXM1, a carcinogenic transcriptional factor, has a critical function in the pathogenesis of various cancers, including liver cancer [43,44]. However, the FOXM1-related upstream regulatory events in LCSCs are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Foxm1 was recently reported to regulate a micro-RNA network which controls the self-renewal capacity in neural stem cells [51]. redPATH provides an interactive plot that can visualize different cell types, cell cycle stages, and gene expression together.…”
Section: Coupling Proliferation With Differentiationmentioning
confidence: 99%
“…NSC mirnome data were obtained from our recently published manuscript [26]. Animal experiments were performed according to the European Community Council Directive 2010/63/EU and were approved by the local Ethics Committee for Animal Experiments (Prot.…”
Section: Methodsmentioning
confidence: 99%
“…Three biological replicates of SHH MB CSCs were subjected to miRNA-sequencing, quality control, mapping, quantification and differential expression analysis was performed between SHH MB CSCs and NSCs, as previously described [26]. In detail, an average of 10.48 ± 0.748 million reads per biological replicate were obtained by the sequencing and quality control was performed using the FastQC tool (, accessed on 01/Februay/2017 before mapping where an average of 92% of reads with a quality score >30 were obtained.…”
Section: Methodsmentioning
confidence: 99%